Photon momentum transfer at water/air interfaces under total internal reflection - Schaberle, Fábio A. (2019)
The transfer of photon momentum at the water/air interface is important for optical manipulation of minute particles and is at the heart of the Minkowski–Abraham controversy.Weuse photoacoustic (PA) detection of ultrasound waves generated when pulsed laser light meets the water/air interface at 3.9 °C(zero thermal expansion), to distinguish momentum transfer from thermoelastic effects. The PA waves dependence on the angle of incidence reveals that momentum transfer maximizes at the critical angle. Momentum transfer is most efficient when the photons travel in water and remain in water after total reflection at the interface, rather than when they cross the interface between dielectric media.